The 1786 acquisition of Pulau Pinang: Unveiling the light letters, revisiting legal history case materials and R. Bonneyâs Kedah 1771â1821 - Merican, A.M. (Penerbit Universiti Sains Malaysia, 2021)
This article reviews the âacquisitionâ of Pulau Pinang by Francis Light and the East India Company (EIC) in the year 1786. The discussion centres on the contested history of Pulau Pinang and the collective memory of the Malays. It reveals discussions between Francis Light and the sultans of Kedah on the supposed âacquisitionâ and sometime leasing of the island to the EIC. It is based on doubts casted by R. Bonney in his 1971 book Kedah 1771â1821: The Search for Security and Independence. This is supported by legal history and the exchanges in the Light Letters between Light and two Kedah rulers. The letters are kept at the Archives of the School of Oriental and African Studies, University of London. This article reveals that there is no agreement of 1786. However the landing of Light at Tanjong Penaga in 1786 has been legitimised in the historiography prompt and proper. Seen from the absence of any treaty, the âacquisitionâ of Pulau Pinang by the EIC in that year is treated as âillegalâ. Â© Penerbit Universiti Sains Malaysia, 2021.